2021
DOI: 10.1002/aesr.202100157
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Unique Structural Chemistry of Sulfur Cathode for High‐Energy Rechargeable Beyond‐Li Batteries

Abstract: The increased demand for energy has prompted users to seek alternative energy storage devices. Post‐Li‐ion battery chemistries have been considered potential contenders for the development of next‐generation battery technologies. The high specific capacity (≈1675 mAh g−1) and high natural abundance (≈953 ppm) of sulfur provide opportunities to meet the rigorous requirements of the market's demands, such as high energy density and low cost. When combined with a high capacity metal anode (e.g., Na ≈ 1165 mAh g−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 277 publications
(407 reference statements)
0
11
0
Order By: Relevance
“…Sulfur cathode has also been employed in various metal-based batteries, such as Li-S, Na-S, and others. [103][104][105][106][107] It has been reported that unstable CEI in these systems can be formed, lowering the overall coulombic efficiency and thus, promoting capacity decay. [108,109] On the other hand, a stable CEI can be formed on sulfur-microporous carbon cathode using fluoroethylene carbonate (FEC) additive in carbonate-based electrolytes.…”
Section: Potential Studies Of Cei In Post-lib Technologiesmentioning
confidence: 99%
“…Sulfur cathode has also been employed in various metal-based batteries, such as Li-S, Na-S, and others. [103][104][105][106][107] It has been reported that unstable CEI in these systems can be formed, lowering the overall coulombic efficiency and thus, promoting capacity decay. [108,109] On the other hand, a stable CEI can be formed on sulfur-microporous carbon cathode using fluoroethylene carbonate (FEC) additive in carbonate-based electrolytes.…”
Section: Potential Studies Of Cei In Post-lib Technologiesmentioning
confidence: 99%
“…Polysulfide dissolution and its shuttling effect are the leading cause of capacity decay and cycling stability in a liquid electrolyte-based RT-Na-S battery. 46,[161][162][163] Tanibata and co-workers devised a strategy to mitigate the capacity decay in a sulfide-based RT-Na-S system. 125 The investigators utilized the Na 3 PS 4 glass-ceramic solid electrolyte and fabricated an all-solid-state RT-Na-S battery.…”
Section: Sulfide-based Isesmentioning
confidence: 99%
“…The energy storing process of these devices takes place in the electrode-electrolyte interface and has a separate path for electron and ion transport. 13,23 Moreover, in their architecture, these EES devices are made up of two electrodes separated by an electrolyte. Fig.…”
Section: Introductionmentioning
confidence: 99%